Literasi Informasi Berbasis Search Engine di SMK PAB 8 Sampali: Literasi Informasi Berbasis Search Engine di SMK PAB 8 Sampali - Wahyu Saptha Negoro; idzhari rahman; Arbana Syamanta (Publikasi Pengabdian Masyarakat, 2023)
Since its birth in the 1960s, the Internet has become an integral part of modern and dynamic society. Several search engines provide a set of tools which, when further explored, will be very useful in shortening search time. The tool includes search techniques using several commands that must be entered into the query by the user. It has been discussed before that there are many search engines (search engines) that can be used to search for information on the internet. However, with all these search engines, Google is still the best. Google is one of the giant companies on the internet. Google has proven to have made a very big contribution to the world community, especially in accessing global information. Advances in science and information technology in the form of internal impact on all aspects of human life. The internet has had a huge impact by penetrating various people's lives and behavior. Keywords : Information Search and Seacrch Engine